Opening words by Lassi Heinenen at the 6th NRF Open Assembly. - Lassi, Heinenen (Arctic Portal, 2011)
Opening words from chair of the Northern Research Forum Steering Committee, Lassi Heininen. Recorded by Arctic Portal at the 6th NRF Open Assembly in Hveragerði Iceland, 4. - 6. September 2011. Please click on the URL below to see the video.